Communication and Collaboration Model of Indonesian Delegation in Myanmar Earthquake Humanitarian Assistance - Hidayat, Muhamad; Mirza, Fajar Iqbal; Riyanto, Budi; Riyadi, Kezia Nariswari (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2025)
This research analyzes the communication and collaboration model of the Indonesian delegation during the humanitarian assistance mission following the 2025 Myanmar earthquake. While natural disasters in Southeast Asia are frequent and require coordinated international responses, the effectiveness of such missions is heavily dependent on communication and collaboration dynamics, especially within politically sensitive environments. This study addresses a specific scholarly gap by empirically examining how a multi-agency delegation's operational model functions in a context of domestic conflict and political instability. The analysis is guided by a synthesized theoretical framework that integrates crisis communication, disaster diplomacy, and collaborative governance theory. Using a qualitative case study approach, data was collected through in-depth interviews with delegation members, document analysis, and participant observation. The findings reveal that the delegation's model, initiated through formal coordination with the Myanmar government and the ASEAN Coordinating Centre for Humanitarian Assistance (AHA Centre), was characterized by an active, adaptive, and highly structured information exchange. The mission's success was enabled by a robust institutional design that included the formation of an agile advance team, and by facilitative leadership that guided the mission's humanitarian and diplomatic objectives. The study contributes to the academic literature by providing a novel application of the Ansell & Gash collaborative governance model to a humanitarian, cross-border context and by offering an empirical example of how disaster diplomacy is operationalized. Practical implications for developing training and guidelines for future international disaster responses are also discussed.Keywords: Communication, collaboration, humanitarian aid, Indonesian delegation, Myanmar earthquake ABSTRAKPenelitian ini menganalisis model komunikasi dan kolaborasi delegasi Indonesia selama misi bantuan kemanusiaan pascagempa bumi Myanmar 2025. Meskipun bencana alam di Asia Tenggara sering terjadi dan membutuhkan respons internasional yang terkoordinasi, efektivitas misi tersebut sangat bergantung pada dinamika komunikasi dan kolaborasi, terutama dalam lingkungan yang sensitif secara politik. Studi ini membahas kesenjangan ilmiah yang spesifik dengan mengkaji secara empiris bagaimana model operasional delegasi multi-lembaga berfungsi dalam konteks konflik domestik dan ketidakstabilan politik. Analisis ini dipandu oleh kerangka teori terpadu yang mengintegrasikan komunikasi krisis, diplomasi bencana, dan teori tata kelola kolaboratif. Dengan menggunakan pendekatan studi kasus kualitatif, data dikumpulkan melalui wawancara mendalam dengan anggota delegasi, analisis dokumen, dan observasi partisipan. Temuan penelitian mengungkapkan bahwa model delegasi, yang diinisiasi melalui koordinasi formal dengan pemerintah Myanmar dan Pusat Koordinasi ASEAN untuk Bantuan Kemanusiaan (AHA Centre), dicirikan oleh pertukaran informasi yang aktif, adaptif, dan sangat terstruktur. Keberhasilan misi ini dimungkinkan oleh desain kelembagaan yang kokoh, yang mencakup pembentukan tim tanggap tanggap, dan kepemimpinan fasilitatif yang memandu tujuan kemanusiaan dan diplomatik misi. Studi ini berkontribusi pada literatur akademis dengan menyediakan aplikasi baru model tata kelola kolaboratif Ansell & Gash dalam konteks kemanusiaan lintas batas, serta dengan menawarkan contoh empiris tentang bagaimana diplomasi bencana dioperasionalkan. Implikasi praktis untuk pengembangan pelatihan dan pedoman bagi respons bencana internasional di masa mendatang juga dibahas.Kata Kunci: Komunikasi, kolaborasi, bantuan kemanusiaan, delegasi Indonesia, gempa bumi Myanmar